Management of Paediatric Ulcerative Colitis, Part 1: Ambulatory Care—An Evidence-based Guideline From European Crohn's and Colitis Organization and European Society of Paediatric Gastroenterology, Hepatology and Nutrition. Issue 2 (August 2018) - Turner, Dan; Ruemmele, Frank M.; Orlanski-Meyer, Esther; Griffiths, Anne M.; de Carpi, Javier Martin; Bronsky, Jiri; Veres, Gabor; Aloi, Marina; Strisciuglio, Caterina; Braegger, Christian P.; Assa, Amit; Romano, Claudio; et al.
ABSTRACT: Background: The contemporary management of ambulatory ulcerative colitis (UC) continues to be challenging with ∼20% of children needing a colectomy within childhood years. We thus aimed to standardize daily treatment of pediatric UC and inflammatory bowel diseases (IBD)-unclassified through detailed recommendations and practice points. Methods: These guidelines are a joint effort of the European Crohn's and Colitis Organization (ECCO) and the Paediatric IBD Porto group of European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN). An extensive literature search with subsequent evidence appraisal using robust methodology was performed before 2 face-to-face meetings. All 40 included recommendations and 86 practice points were endorsed by 43 experts in Paediatric IBD with at least an 88% consensus rate. Results: These guidelines discuss how to optimize the use of mesalamine (including topical), systemic and locally active steroids, thiopurines and, for more severe disease, biologics. The use of other emerging therapies and the role of surgery are also covered. Algorithms are provided to aid therapeutic decision-making based on clinical assessment and the Paediatric UC Activity Index (PUCAI). Advice on contemporary therapeutic targets incorporating the use of calprotectin and the role of therapeutic drug monitoring are presented, as well as other management considerations around pouchitis, extraintestinal manifestations, nutrition, growth, psychology, and transition. A brief section on disease classification using the PIBD-classes criteria and IBD-unclassified is also part of these guidelines. Conclusions: These guidelines provide a guide to clinicians managing children with UC and IBD-unclassified management to provide modern management strategies while maintaining vigilance around appropriate outcomes and safety issues. Abstract : Supplemental Digital Content is available in the text